Моделювання динамічних навантажень із зміною схеми з'єднання фаз асинхронного двигуна "трикутник – зірка" - Попович, О.М. (Електротехніка і електромеханіка, 2011)
At modeling of dynamic conditions of delta-to-star conversion of stator phase connection by means of a developed mathematical model of an asynchronous motor, feasibility of dynamic load dropping is investigated.